BiVO4-based nanoparticles for visible light photocatalytic applications - Han, Mandi (2014)
In recent years, clean renewable energy and sustainable environment are emerging as the top issues and challenges for humanity. Photocatalysis can be applied to convert solar energy into chemical energy, and is considered as an attractive strategy to tackle the environmental and energy challenges. Since the traditional photocatalyst TiO2 is limited in ultraviolet (UV) range applications, alternative materials have been widely explored. Among them, BiVO4 has shown great potential to extend beyond the UV region due to its suitable band-gap of 2.4 eV and favorable band edge alignment to water splitting. In this work, monoclinic m-BiVO4 nanoparticles were synthesized and surface-modified in order to improve the photocatalytic property.